PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU - Nusi, Cindi Anggriani; Panigoro, Meyko; Ardiansyah, Ardiansyah; Mahmud, Melizubaida; Sudirman, Sudirman (Universitas Negeri Gorontalo, 2024)
In general, Integrated Social Studies subjects in elementary schools (SD / MI) are considered very boring subjects so that by innovating learning is expected to have an impact on learning outcomes. This research aims to determine the extent of the influence of the problem-based learning (PBL) model on the students learning outcomes in the Integrated Social Science subject for Class VIII of SMP Negen 3 Limboto, Gorontalo Regency. The research employs a quantitative approach, a correlational quantitative method with a sample size of 51 students. Data collection techniques include observation, questionnaires, documentation, and data analysis techniques involving simple regression. The results indicate a positive and significant influence of the Problem-Based Learning (PBL) model on the students' learning outcomes in Integrated Social Science subject for Class VIII of SMP Negeri 3 Limboto, Gorontalo Regency. The coefficient of determination obtained from the regression model is 0,537, indicating that 53,7% of the variation in learning outcomes is explained by implementing the problem-based learning (PBL) model during the learning activities. In other words, the better the teacher implements the problem-based learning (PBL) model, the higher the students' leaming outcomes. Other variables not examined in this research influence the remaining 46,3% of the students' performance.